1989
DOI: 10.1002/jcu.1870170207
|View full text |Cite
|
Sign up to set email alerts
|

Ultrasound‐guided puncture of cystic tumors in the lower pelvis of young women

Abstract: During the period from 1984 through 1986, 72 ultrasound-guided cyst punctures were performed in 60 young women (less than or equal to 40 years). Thirty-one punctures were performed using the transabdominal route and 41 punctures under the guidance of endovaginal scanning. General or local anesthesia were used in 97% of the transabdominal punctures while the corresponding figure for the endovaginal technique was 49%. Seventy-seven percent (46/60) of the women developed no new cysts within one year of the last p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
12
1

Year Published

1993
1993
2013
2013

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(13 citation statements)
references
References 11 publications
0
12
1
Order By: Relevance
“…It is noteworthy that in our study all women escaped immediate surgical inter vention. The recurrence rate within 1 year of the proce dure was 11.1%, which is lower than that reported in a previous study (23%) [5].…”
Section: Discussioncontrasting
confidence: 53%
See 1 more Smart Citation
“…It is noteworthy that in our study all women escaped immediate surgical inter vention. The recurrence rate within 1 year of the proce dure was 11.1%, which is lower than that reported in a previous study (23%) [5].…”
Section: Discussioncontrasting
confidence: 53%
“…Recently, in cases of twisted ovarian cysts, laparoscopic aspiration and unwinding the cysts has been suggested [3,4], Laparotomy is thus prevented, with important impli cations for future fertility. Preservation of future fertility also motivated the introduction of ultrasound-guided puncture of 'simple' ovarian cysts [5,6], In comparison with laparoscopic aspiration and unwinding of twisted ovarian cysts, ultrasound-guided puncture may mean even less risk of pelvic adhesions, and may additionally reduce morbidity associated with general anaesthesia.…”
Section: Introductionmentioning
confidence: 99%
“…1,15,18 In spite of skepticism and initial resistance, the aspiration of adnexal cysts with sonographic benign criteria is now employed not only as a diagnostic tool 2,16,17,[22][23][24]31,32 but also as treatment for nonneoplastic cysts. 5,7,10,12,14,20,21,30 This rapid and well-tolerated procedure has been used for aspiration of cysts in pregnant women 11,14 and prenatally, 3,27 but, like any other invasive techniques, it is not absolutely risk free. 9,16,19 Consequently, its therapeutic indications 34 and diagnostic value are subject to ongoing debate, especially because of the low sensitivity 4,6,24 and occasional false positive result, 25,28,29 even when carried out by expert cytopathologists.…”
mentioning
confidence: 99%
“…Ultrasound guided cyst aspiration allows both cytologic analysis of the cyst content and a treatment option. Several studies have demon-strated that cyst aspiration was found as the successful definitive treatment in more than 65% of the cases [10][11][12][13]. Cyst aspiration bears another important advantage as a means of relieving acute pain, thus preventing an urgent operative procedure on symptomatic functional cysts which are destined to resolve [15][16][17].…”
Section: Discussionmentioning
confidence: 99%
“…Secondly the higher resolution of the new ultrasound machines, as well as the introduction of vaginal transducers has caused a revolution in the ability to distinguish between benign and malignant lesions [7,9]. This has led some investigators to perform cyst aspiration in cases with benign sonographic appearance, by ultrasonographically guided needle puncture [10][11][12][13]. Cyst puncture may be more advantageous during pregnancy, as it can save the patient from having laparotomy which has the potential for causing abortion.…”
Section: Introductionmentioning
confidence: 99%